MENGENAL DUNIA KTSP (Optimalisasi Peran KTSP di Lembaga Pendidikan) - Baharuddin, Baharuddin (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2009)
Indonesia is a country that never consistent to deal with its educational system (i.e. curriculum). This phenomenon can be seen through the changing of curriculum during 1968, 1975, 1984, 2004, and 2006. The last curriculum development (i.e. in 2006) is called as KTSP (kurikulum tingkat satuan pelajaran). The purpose of KTSP is to design curriculum which based on educational autonomy. This curriculum development indicates that the curriculum will train Indonesian human resources to adapt the challenges of social changes. Key Word: KTSP, Kurikulum, Pendidikan, Guru dan Siswa, Sekolah/Madrasah